Tantangan transisi energi terbarukan di Indonesia: (Studi kasus PLTS di Kabupaten Cilacap) - Sofian Manahara; Sheila Kusuma Putri; Imaniar Septa Kencana W (Journal of Innovation Materials, Energy, and Sustainable Engineering, 2023)
The use of new, renewable Energy has been initiated since the promulgation of Law Number 30 of 2007 concerning Energy. Now, the urgency is starting to appear with the enactment of Presidential Regulation Number 112 of 2022 concerning the Acceleration of Renewable Energy Development for the Supply of Electric Power. Solar thermal Energy is very abundant in areas with tropical climates, such as Indonesia, which is always illuminated by the sun all year round. This is an energy source that has great potential to be developed. PT One of the locations for implementing PLTS by PT X is in the Cilacap Regency. PLTS, with a capacity of 1,340 kiloWatts with electricity production of 833 MWh and an investment value of IDR 10 billion per 1 MW, operational since August 2021, is used to support the provision of electrical energy sources for office activities and employee housing, with an average reduction in equivalent CO2 emission intensity of 7.60 %. Implementation of the use of PLTS still faces various challenges, especially for commercial use, such as a complicated licensing process that is not yet aligned between authorized agencies, the limited availability of PLTS infrastructure and technology and supporting facilities such as electricity transmission networks in Indonesia, thus affecting the investment value or installation costs, limitations human resources during the Covid-19 pandemic, to allegations that political factors and conflicts of interest between electricity supply sectors cause the minimal use of PLTS. On the other hand, considering that significant climate change is starting to be seen and felt, the existence of PLTS is expected to accelerate the achievement of reducing greenhouse gas emissions. This paper will provide an overview of the implementation of PLTS use for the commercial sector, which has been carried out as evaluation material for all parties to prepare environmentally sound sustainable development strategies through the implementation of PLTS use.